Remote simulation: A qualitative study on clinical reasoning and cognitive errors from the students’ perspective - Mir-Bezanilla, Verónica; González-Bernstein, Antonia; Lüer-Sepúlveda, María Ignacia; López-Leiva, Rosario; Díaz-Schmidt, Joaquín; Armijo-Rivera, Soledad; Pérez-Villalobos, Cristhian (Salud, Ciencia y Tecnología - Serie de Conferencias, 2023)
Introduction: Clinical reasoning is a crucial competency for medical practice and also a complex theory that is susceptible to cognitive errors. It is usually taught with clinical cases, in clinical settings, without technologies and in a practical manner rather than from a conceptual perspective. Given the need to improve its teaching in the undergraduate medical curriculum during the pandemic, we hypothesized that medical students participating in an online simulation and reflective practice course could benefit from a practical and theoretical approach to the clinical reasoning process. Material and Methods: A four-week online course, based on synchronous and asynchronous online simulation and reflective practice, was developed to promote metacognition among participants. The course was delivered to 8 sixth-year medical students as an elective module. A questionnaire consisting of four open-ended questions was designed to explore knowledge about clinical reasoning and cognitive errors, and was administered at the beginning and end of the course. A qualitative analysis of the responses was carried out using Berelson’s content analysis method. Results: At the end of the course, students changed their understanding of the concept of clinical reasoning, considering it more as a process and identifying the dual nature described in one of the theories of clinical decision making. They also changed their knowledge of cognitive errors, attributing them not only to lack of knowledge, and understanding that they can actively use some strategies to reduce cognitive biases. Discussion: This study confirms that undergraduate students positively change their concept of clinical reasoning and their knowledge about this cognitive process and the cognitive errors that occur in it after a course that includes online simulation and reflection.